Effect of hay type on cecal and fecal microbiome and fermentation parameters in horses and efficacy of varying protein sources on feedlot goat performance - Sorensen, Rachel Jean (Kansas State University, 2019)
Six cecally cannulated horses were used in a split plot design in a 2-period crossover. Each period consisted of a 21-d acclimation to hay type followed by a 24-h sample collection. Whole plot consisted of hay type (cool-season grass hay and legume hay) with subplots of sampling location (cecum and rectum) and hour. Fecal and cecal samples were collected every 3 h and analyzed for pH, volatile fatty acids (VFA) and the V4 region of the 16S rRNA gene was sequenced using Illumina HiSeq. Horses fed alfalfa had greater (P ≤ 0.05) fecal than cecal pH, whereas horses fed brome had greater (P ≤ 0.05) cecal than fecal pH. Regardless of hay type, total VFA concentrations were greater (P ≤ 0.05) in cecal fluid than in feces, and alfalfa resulted in greater (P ≤ 0.05) VFA concentrations than brome in both sampling locations. Alpha diversity was greater (P ≤ 0.05) in fecal compared to cecal samples. Microbial community structure within each sampling location and hay type differed from one another (P ≤ 0.05). In all, fermentation parameters and bacterial populations were impacted by hay type and sampling location. Two experiments were conducted to evaluate impact of varying protein source on feedlot goat performance. In experiment 1 the effects of feeding dried distillers grains with solubles (DDGS) in place of soybean meal (SBM) on growth, economic efficiency, carcass characteristics, backfat fatty acid profiles, and fecal microbiome of Boer-type goats were evaluated. Forty-eight goats were assigned to 1 of 4 dietary treatments consisting of 0% (0DDGS), 10.3% (10DDGS), 20.5% (20DDGS), or 31.1% (30DDGS) DDGS replacing SBM in the total diet. Inclusion of DDGS linearly improved (P = 0.02) ADG, while feed cost/kg gain decreased (P < 0.0001). There were no discernible differences in fecal percentages of Bacteroidetes (P = 0.36) and Firmicutes (P = 0.12) among treatments. Polyunsaturated fatty acids tended to quadratically increase (P = 0.06) with increased DDGS inclusion. In experiment 2, 75 Boer-type goats were assigned randomly to 1 of 5 dietary treatments consisting of SBM with Ammonia Chloride (AmCl; SBM+AmCl), DDGS with AmCl (DDGS+AmCl), SoyPlus (Dairy Nutrition Plus, Ames, IA) with AmCl (SoyPlus+AmCl), SBM with SoyChlor (Dairy Nutrition Plus Ames, IA; SBM+SoyChlor), and SoyPlus with SoyChlor (SoyPlus+SoyChlor). SoyChlor improved ADG (P = 0.01), feed efficiency (P = 0.04), and value of gain (P = 0.01) when compared to AmCl. SoyPlus had no effect on ADG (P > 0.10) when compared to SBM. Protein source did not alter Firmicutes:Bacteroidetes (P > 0.10). Goats fed SBM+AmCl had greater (P = 0.04) abundance of Bacteroidetes than goats fed DDGS+AmCl. No differences were detected in alpha and beta diversity measures. Loin eye area was greater in goats fed SBM compared to SoyPlus (P = 0.05) or DDGS (P = 0.04), regardless of chloride source. Alternative protein sources in goats may improve feed cost/kg gain without negatively impacting goat performance.
Keywords: Goat; Horse; Hay type; Microbiome; Protein